Alleged predisposing dietary factors fail to increase the incidence of osteochondrosis-like lesions in growing pigs at 14 and 24 wk of age. (6th April 2020) - Grez-Capdeville, Mariola; Gross, Nicole; Baker, Joni C; Shutter, Jennifer A; Haas, Amanda R; Wilson, Mark E; Crenshaw, Thomas D
Abstract: Early lesions of osteochondrosis (OC ) are exhibited by regions of cartilage retention along the growth plate and articular cartilage. Progression of OC lesions may impair locomotion and necessitate euthanasia in adherence to animal welfare guides. Little is known about the role of nutrition in the initiation and early stages of OC. However, dietary components are commonly implicated as predisposing factors. In this study, diets were altered as an attempt to induce early stage OC lesions under controlled conditions. At 8 wk of age, 96 crossbred gilts (body weight [BW ] = 17.4 ± 0.18 kg) were randomly assigned to one of four corn-soybean meal-based diets (four pens per diet, six pigs per pen) to assess diet effects on the number and volume of OC lesions in the distal femur. Diets included a non-pelleted control diet (Ctl ); Ctl plus 20% glucose (Glc ); the Ctl with increased concentrations of lysine, Ca, and P (+CaP ); and the +CaP diet in a pelleted form (PEL ). Femurs were collected from pigs euthanized at either 14-wk (Wk 14) or 24-wk (Wk 14) of age for assessments of OC lesions. Based on a mixed model analysis with pen as the experimental unit, dietary treatments did not affect final BW (129.3 ± 3.8 kg) or average daily gain (ADG) (1.00 ± 0.03 kg/d) over the trial. As expected, pigs fed PEL and Glc diets were more efficient ( P < 0.05) in feed conversion compared with Ctl and +CaP. Using femurs as the experimental unit at Wk 14 (collected from two of the six pigs per pen), bone mineral content, determined by dual-energy x-ray absorptiometry scans, was greater ( P < 0.05) in pigs fed +CaP and PEL than Ctl or Glc diets; however, only +CaP group differed ( P < 0.05) at Wk 24 (collected from four pigs per pen). Computed tomography (CT ) scans of femurs were reconstructed as three-dimensional images to allow detection of the number, volume, and surface area of lesions in distal growth plates. At Wk 14, pigs fed Ctl had fewer number of lesions ( P < 0.05); however, no differences were detected among dietary treatments in lesion volume or lesion surface area. Pigs had fewer lesions at Wk 24 than Wk 14; however, differences were not detected among dietary treatments. At Wk 24, pigs fed Ctl diets had the greatest lesion volume among dietary treatments ( P < 0.05). In conclusion, none of the pigs exhibited symptoms of lameness regardless of dietary treatment or OC lesion traits. Diet modifications due to pelleting or inclusion of rapidly digestible ingredients, such as glucose, did not increase prevalence or size of OC lesions. Image analysis of CT scans was a reliable method to quantify the number, size, and location of OC lesions.